INFLUENCING FACTORS OF DIGITAL CHANNEL USAGE TO SUBSCRIBE INTERNET SERVICE - Imamul Akhyar; Nita Garnida (International Journal of Accounting, Finance and Business, 2021)
In 2020, Pandemic of COVID-19 shocked the world and has been affecting manyaspects of life, from economy to lifestyle. People begin to change their habit and adapt to theâ€œnew normalâ€ by shifting their routine outside activities into at home internet-based activities,such as online shopping and online learning. This situation becomes the opportunity forinternet-based business, including Indihome, an internet service provider in Indonesia, toacquire more customers from digital sales channels. This research is intended to examinefactors that influence the usage of digital channels to subscribe Indihome internet servicesusing a modified technology acceptance model (TAM) approach. We applied quantitativeonline survey to 204 internet users and used structural equation model to measure therelationship among TAM variables. The result showed that perceived ease of use and perceivedusefulness significantly and positively influence consumers attitude toward the use of digitalchannel to subscribe internet service. While level of income significantly influences perceivedusefulness of digital channel, we also found that consumersâ€™ perceived access barrier such asconfidentiality of personal data and capability does not have significant effect on consumerattitude toward the use of digital channel. Last, as the managerial implication, this studyprovides key insights for managers to develop digital channel strategy based on researchfindings.